2014
DOI: 10.1021/om500506y
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Oxidative Addition in Nickel-Catalyzed Alkyl–Aryl Kumada Coupling Reactions

Abstract: The mechanism of alkyl-aryl Kumada coupling catalyzed by the nickel pincer complex Nickamine was studied. Experiments using radical-probe substrates and DFT calculations established a bimetallic oxidative addition mechanism. Kinetic measurements showed that transmetalation rather than oxidative addition was the turnover determining step. The transmetalation involved a bimetallic pathway.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 52 publications
6
38
1
Order By: Relevance
“…Tertiary halides were shown to be unreactive due to a prohibitively high barrier of reductive elimination relative to the most stable triplet Ni(II) intermediate. 305 The authors concluded that the aryl−alkyl coupling involved a Ni(I)/Ni(III) catalytic cycle, in which the transmetalation was deduced to be the turnover-determining step. The authors also suggested that the transmetalation may involve a bimetallic pathway, in which two Ni(II) complexes are required to supply two electrons to the alkyl halide.…”
Section: Suzuki Couplingmentioning
confidence: 99%
“…Tertiary halides were shown to be unreactive due to a prohibitively high barrier of reductive elimination relative to the most stable triplet Ni(II) intermediate. 305 The authors concluded that the aryl−alkyl coupling involved a Ni(I)/Ni(III) catalytic cycle, in which the transmetalation was deduced to be the turnover-determining step. The authors also suggested that the transmetalation may involve a bimetallic pathway, in which two Ni(II) complexes are required to supply two electrons to the alkyl halide.…”
Section: Suzuki Couplingmentioning
confidence: 99%
“…75 sp 2 -Hybridized electrophiles 55 undergo oxidative addition selectively and rapidly in the presence of nickel(0) species such as 56 , thereby producing nickel(II) complex 57 . Bimetallic oxidative addition 76 of alkyl halide 58 leads to transient nickel(III) species 59 . Rapid reductive elimination then produces nickel(I) intermediate 60 and the C sp 3 -C sp 2 product 61; 60 is then reduced to the active nickel(0) catalyst 56 by a low-valent metal reducing agent to complete the catalytic cycle.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…In contrast with nickel's well‐known affinity towards radicals, generation of radical species by nickel complexes is less documented but has been implicated in nickel‐catalyzed cross‐coupling reactions ,,. Metal‐centered redox transfers are involved in these examples but possible implication of a bipyridine ligand by delocalization of electronic density was reported in the nickel‐based formation of carbon‐centered radicals from an alkyl halide .…”
Section: Figurementioning
confidence: 99%